Mucocutaneous presentations of consultant critical and non-critical cases of admitted COVID-19 patients, outpatients and vaccine-associated dermatoses: a large original study of a general COVID-19 centers from Iran - Afsaneh Sadeghzadeh-Bazargan; Azadeh Goodarzi (PAGEPress Publications, 2023)
Rapid and proper diagnosis of mucocutaneous presentations of COVID-19 which in many cases, are representing internal organ damages is a key way for a better approach to these patients, which could be even lifesaving. In this original study, we reported consultant critical and non-critical cases of admitted COVID-19 patients and some interesting outpatient cases during 14 months and some newly encountered vaccine-associated dermatoses. We presented 121 cases divided into 12 categories; all had full multi-aspects photographs attached as an atlas to a Supplementary File. These categories were:1- Generalized papulopustular eruptions (3 patients), 2- Erythroderma (4 patients), 3- Maculopapular lesions(16 patients), 4- Mucosal lesions (8 patients), 5- Urticarial lesions and angioedema (16 patients), 6- Vascular injuries (22 patients), 7- Vesiculobullous lesions (12 patients), 8- The specific new onset of mucocutaneous presentations or aggravation of any especial previous dermatoses (9 patients), 9- Nail changes (3 patients), 10- Hair loss (2 patients), 11- Non-specific mucocutaneous problems (16 patients) and 12-Vaccine-associated dermatoses (10 patients).In the pandemic, if we countered with extensive mucocutaneous lesions with vascular components or vesiculobullous erosive lesions in association with any cutaneous rash that could be an alarming sign of a probable life-threatening systemic event, we would need to approach them as soon as possible.